Review of Smart Contracts for Cloud-Based Manufacturing - Hassan Afridi, Ahmad (Computing and Informatics, 2022)
Cloud-based manufacturing is taking shape, and many industries seem interested to make the transition to it. Developing blockchain solutions for trusted computing is also taking its roots. Developing a blockchain-based solution for cloud-based manufacturing systems is a field that is new but also faces limitations and a lack of case studies. Smart contracts are one part of the solution which deals with making blockchain successful in cloud-based manufacturing. As we move towards smart contracts design and development for cloud-based manufacturing, there is no complete survey of smart contract and cloud manufacturing that can highlight critical, challenging issues and limitations. Most of the work found in smart contracts is mostly financial and notary-centric applications. On the cloud manufacturing side, most of the literature deals with Internet of Things (IoT) and cloud computing systems. Therefore, there is a need to study the best practices to start manufacturing supported by blockchain smart contracts. We conducted a scoping review for smart contracts for cloud manufacturing to address the problem mentioned above. We studied the latest case studies and concepts in data extracted from digital libraries and online repositories. Furthermore, we follow the relevance and acceptance criteria of research articles for inclusion and exclusion from this work. This paper focuses on blockchain systems, smart contracts and architecture, smart contracts in the cloud, and the IoT environment. Furthermore, we tried to bridge design and implementation details for readers to understand the patterns that can replicate for cloud-based manufacturing systems.